In vitro identification of human cytochrome P450 isoforms involved in the metabolism of Geissoschizine methyl ether, an active component of the traditional Japanese medicine Yokukansan. (2nd April 2016) - Matsumoto, Takashi; Kushida, Hirotaka; Maruyama, Takeshi; Nishimura, Hiroaki; Watanabe, Junko; Maemura, Kazuya; Kase, Yoshio
Abstract: 1. Yokukansan (YKS) is a traditional Japanese medicine also called kampo, which has been used to treat neurosis, insomnia, and night crying and peevishness in children. Geissoschizine methyl ether (GM), a major indole alkaloid found in Uncaria hook, has been identified as a major active component of YKS with psychotropic effects. Recently, GM was reported to have a partial agonistic effect on serotonin 5-HT1A receptors. However, there is little published information on GM metabolism in humans, although several studies reported the blood kinetics of GM in rats and humans. In this study, we investigated the GM metabolic pathways and metabolizing enzymes in humans. 2. Using recombinant human cytochrome P450 (CYP) isoforms and polyclonal antibodies to CYP isoforms, we found that GM was metabolized into hydroxylated, dehydrogenated, hydroxylated+dehydrogenated, demethylated and water adduct forms by some CYP isoforms. 3. The relative activity factors in human liver microsomes were calculated to determine the relative contributions of individual CYP isoforms to GM metabolism in human liver microsomes (HLMs). We identified CYP3A4 as the CYP isoform primarily responsible for GM metabolism in human liver microsomes. 4. These findings provide an important basis for understanding the pharmacokinetics and pharmacodynamics of GM and YKS.